EFEK APLIKASI KALENG PERANGKAP NYAMUK TERHADAP DENSITAS AEDES - - Sayono (Jurnal Kesehatan Masyarakat Indonesia, 2011)
Background; Aedes mosquitoes are the arboviruses diseases vectors, including Yellow Fever, Dengue and Dengue Hemorrhagic Fever, and Chikungunya, that often cause an epidemic. The main control methods for those disease is conducted the vector control program, to reduce the Aedes indices. Various ovitrap modification resulted the productive lethal trap, such as mosquito trap tin (MTT), but the evaluation of intervention impact of this model to the Aedes indices is needed. Objective: to understand the impact of MTT intervention to the Aedes indices. Method: the lethal mosquito trap-tin were made from the discharge-tin, covered by mosquito net proper in the water surface. The brood water was made from 10% of the shrimp rinse water. Every house were placed 4 tin; indoor and outdoor for 4 week. Aedes indices were calculated every week. Results: indoor OI reduced consistently from 60,5% to 36,4%, respectively. Overall, reducing of OI were   20,5%. Reduction of HI in treatment group was higher then the control one, while CI and BI were not induced. Conclusion: Using of MTT can reduce the Aedes density up to 20,5%. This model can be an alternative property in arboviruses vector control, especially DHF, but the advance experiment is needed. Key words: mosquito trap tin, Aedes index,arboviruses, ovitrap